Bt rice in China — focusing the nontarget risk assessment. Issue 10 (18th April 2017) - Li, Yunhe; Zhang, Qingling; Liu, Qingsong; Meissle, Michael; Yang, Yan; Wang, Yanan; Hua, Hongxia; Chen, Xiuping; Peng, Yufa; Romeis, Jörg
Summary: Bt rice can control yield losses caused by lepidopteran pests but may also harm nontarget species and reduce important ecosystem services. A comprehensive data set on herbivores, natural enemies, and their interactions in Chinese rice fields was compiled. This together with an analysis of the Cry protein content in arthropods collected from Bt rice in China indicated which nontarget species are most exposed to the insecticidal protein and should be the focus of regulatory risk assessment.